Do Lifestyle, Price and Quality of Goods Influence Muslim Consumers' Used Clothing Purchasing Decisions - Sayidina, Novearnetha Noor; Butin, Dinawati; Yeubun, Shimah Fauziah; Affandy, Fachrudin Fiqri (Journal of Islamic Economics Perspectives, 2024)
The aim of conducting research on the factors that are considered in selecting and purchasing the interest in buying used clothes (thrifting) among IAIN Fattahul Muluk Papua students is to find out and see how important the factors that influence purchasing are to the buying interest of consumers. This research uses quantitative methods. The respondents in this research were IAIN Fattahul Muluk Papua students through a questionnaire, and this research can draw the conclusion that selection and purchasing influence students' interest in buying second-hand clothes (thrifting). Used clothes are very popular, especially in urban areas. Consumers' interest in buying second-hand clothes is very high, this is related to the lifestyle of modern society which is increasingly increasing, with the price range being more affordable and the quality of second-hand clothes still being good. A high lifestyle greatly influences consumers in consuming goods, the lifestyle factor itself will also influence the quality and price of the product. Factors that significantly influence consumers' buying interest in used clothing are price and quality.